Combined NGS Approaches Identify Mutations in the Intraflagellar Transport Gene IFT140 in Skeletal Ciliopathies with Early Progressive Kidney Disease. Issue 5 (11th April 2013) - Schmidts, Miriam; Frank, Valeska; Eisenberger, Tobias; al Turki, Saeed; Bizet, Albane A.; Antony, Dinu; Rix, Suzanne; Decker, Christian; Bachmann, Nadine; Bald, Martin; Vinke, Tobias; Toenshoff, Burkhard; et al.
<x xml:space="preserve">Abstract</x> Jeune Asphyxiating Thoracic Dysplasia (JATD) is a rare recessive ciliary chondrodysplasia associated with death in infancy due to respiratory failure, and extraskeletal symptoms also occur in some patients. This large next generation sequencing study in 66 JATD and Mainzer‐Saldino syndrome (MSS) families reveals that mutations in the intraflagellar transport protein IFT140 cause MSS and are a frequent cause of JATD with retinal and kidney symptoms but mild thorax phenotype, providing for the first time a clinically significant genotype‐phenotype association in JATD. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>